2014
DOI: 10.7202/1027830ar
|View full text |Cite
|
Sign up to set email alerts
|

Le craving comme symptôme central de la toxicomanie : de ses fondements neurobiologiques à sa pertinence clinique

Abstract: Le craving, ce désir intense de consommer, est un symptôme central de la toxicomanie. Jusqu’au début des années 2000, peu d’outils existaient afin d’étudier le phénomène de manière plus concrète pour mieux le définir, le comprendre et approfondir les fondements neurobiologiques qui le sous-tendent. Avec les avancées technologiques des dernières années (IRM fonctionnelle, PET Scan), puis l’arrivée du DSM-V et son inclusion comme critère diagnostique des troubles liés à l’utilisation de substances, le craving es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
2
0
2
Order By: Relevance
“…Neurobiological research on addiction has revealed the existence of a common mechanism between substance addiction and behavioural addictions (Leeman & Potenza, 2013;Weinstein & Lejoyeux, 2015). Regarding similarities between MP overuse/nomophobia and substance addiction, the results of different studies (Cheung & Wong, 2011;Gao et al, 2018;Jenaro et al, 2007;Morissette et al, 2014;Ozturk et al, 2013;Reed et al, 2015;Thomée et al, 2011) indicate a variety of adverse effects for health, such as depression, social anxiety, insomnia, and hyperactivity. Further studies about these problems are necessary and specific tools to assess these constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Neurobiological research on addiction has revealed the existence of a common mechanism between substance addiction and behavioural addictions (Leeman & Potenza, 2013;Weinstein & Lejoyeux, 2015). Regarding similarities between MP overuse/nomophobia and substance addiction, the results of different studies (Cheung & Wong, 2011;Gao et al, 2018;Jenaro et al, 2007;Morissette et al, 2014;Ozturk et al, 2013;Reed et al, 2015;Thomée et al, 2011) indicate a variety of adverse effects for health, such as depression, social anxiety, insomnia, and hyperactivity. Further studies about these problems are necessary and specific tools to assess these constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Патогенетическое родство алкоголизма и расстройств, ассоциированных с тревогой, определяется, в частности, тем, что общей основой тревоги и потребности индивида в алкоголе служит нарушение нейротрансмиссии норадреналина, серотонина и ГАМК [2,3]. В то же время психотропные и наркогенные эффекты 2 алкоголя и других ПАВ обусловлены влиянием на нейротрансмиссию ГАМК, дофамина, серотонина и других нейротрансмиттеров, что способствует в числе прочих причин возникновению сопутствующих психических нарушений, включая тревогу, у пациентов наркологической клиники.…”
Section: Yup Sivolap Sechenov First Moscow State Medical Universityunclassified
“…Префронтальная кора, миндалина, прилежащее ядро, а также бледный шар, вентральная область покрышки и ряд других отделов мозга образуют церебральную систему награды (англ. : reward system), измененное функционирование которой лежит в основе злоупотребления ПАВ и нехимических зависимостей 2. Под наркогенными эффектами, или аддиктивным потенциалом вещества (abuse potential), понимают его способность вызывать пристрастие и зависимость 3.…”
unclassified
“…According to many smokers, craving is the major reason for failing or not attempting to stop. This concept has been described as 'an abnormal desire or need to take a drug' 2 , including conscious and unconscious aspects. Although a large consensus supports the importance of craving, this construct remains complex to define and explain [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%